2016
DOI: 10.1016/j.neuroimage.2016.04.029
|View full text |Cite|
|
Sign up to set email alerts
|

Cortical complexity as a measure of age-related brain atrophy

Abstract: The structure of the human brain changes in a variety of ways as we age. While a sizeable literature has examined age-related differences in cortical thickness, and to a lesser degree, gyrification, here we examined differences in cortical complexity, as indexed by fractal dimensionality in a sample of over 400 individuals across the adult lifespan. While prior studies have shown differences in fractal dimensionality between patient populations and age-matched, healthy controls, it is unclear how well this mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
255
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(286 citation statements)
references
References 87 publications
(135 reference statements)
27
255
4
Order By: Relevance
“…Unlike other studies in adults (e.g. Madan & Kensinger, 2016;Yotter et al, 2011), we did not find that fractal dimension was a particularly sensitive measure, but this index of surface area is, at present, underexplored in developmental populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike other studies in adults (e.g. Madan & Kensinger, 2016;Yotter et al, 2011), we did not find that fractal dimension was a particularly sensitive measure, but this index of surface area is, at present, underexplored in developmental populations.…”
Section: Discussioncontrasting
confidence: 99%
“…We analyzed cortical thickness, surface area (gyrification), and surface complexity (fractional dimension; Yotter, Nenaduc, Ziegler, Thompson & Gaser, 2011) of the right IFG. All of these measures have been shown to provide complimentary information about individual differences and development (Madan & Kensinger, 2016). Cortical thickness is an established surfacebased measure known to be associated with conscientiousness (Riccelli, Toschi, Nigro, Terracciano, & Passamonti, 2017), just like gyrification (Riccelli et al, 2017), but gyrification may be particularly sensitive to developmental differences (Klein et al, 2014).…”
Section: Surface-based Morphometrymentioning
confidence: 99%
“…Recently we demonstrated that age-related differences in the shape, i.e., structural complexity, of cortical regions were more pronounced than in cortical thickness or gyrification (Madan & Kensinger, 2016). Moreover, we found that complexity statistically accounted for all of the age-related differences associated with cortical thickness and gyrification.…”
Section: Introductionmentioning
confidence: 99%
“…Human brains undergo morphometric changes over a lifetime, from conception through to birth, infancy, adolescence, adulthood, and old age (Thambisetty et al (2010); Madan and Kensinger (2016)). This is further compounded by the changes associated with various brain pathologies such as tumours (e.g.…”
Section: Discussionmentioning
confidence: 99%